Macrocognition in Day-To-Day Police Incident Response - Baber, Chris; McMaster, Richard (Frontiers in Psychology, 2016)
Using examples of incidents that UK Police Forces deal with on a day-to-day basis, we explore the macrocognition of incident response. Central to our analysis is the idea that information relating to an incident is translated from negotiated to structured and actionable meaning, in terms of the Community of Practice of the personnel involved in incident response. Through participant observation of, and interviews with, police personnel, we explore the manner in which these different types of meaning shift over the course of incident. In this way, macrocognition relates to gathering, framing and sharing information through the collaborative sensemaking practices of those involved. This involves two cycles of macrocognition, which we see as ‘informal’ (driven by information gathering as the Community of Practice negotiates and actions meaning) and ‘formal’ (driven by the need to assign resources to the response and the need to record incident details). The examples illustrate that these cycles are often intertwined, as are the different forms of meaning, in situation-specific ways that provide adaptive response to the demands of the incident.